2017
DOI: 10.1093/heapol/czx054
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Interventions for Newborns in Ethiopia (COMBINE): Cost-effectiveness analysis

Abstract: About 87 000 neonates die annually in Ethiopia, with slower progress than for child deaths and 85% of births are at home. As part of a multi-country, standardized economic evaluation, we examine the incremental benefit and costs of providing management of possible serious bacterial infection (PSBI) for newborns at health posts in Ethiopia by Health Extension Workers (HEWs), linked to improved implementation of existing policy for community-based newborn care (Health Extension Programme). The government, with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 11 publications
0
44
1
Order By: Relevance
“…[5][6][7][8][9][28][29] Experience from Ethiopia also showed that implementing neonatal PSBI management within the existing government health structure through Health Extension Workers at community level was feasible and cost effective. [30]Its inclusion in the intervention areas reduced the post day 1 neonatal deaths by 17% compared to control areas. Also in a similar setting in Nepal, a community-based pilot called-Morang Innovative Neonatal Intervention (MINI) progamme, implemented withing the existing government health infrastructure, showed that Community Health Workers were able to assess and identify possible infections in young infants and delivered appropriate treatment with antibiotics.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[5][6][7][8][9][28][29] Experience from Ethiopia also showed that implementing neonatal PSBI management within the existing government health structure through Health Extension Workers at community level was feasible and cost effective. [30]Its inclusion in the intervention areas reduced the post day 1 neonatal deaths by 17% compared to control areas. Also in a similar setting in Nepal, a community-based pilot called-Morang Innovative Neonatal Intervention (MINI) progamme, implemented withing the existing government health infrastructure, showed that Community Health Workers were able to assess and identify possible infections in young infants and delivered appropriate treatment with antibiotics.…”
Section: Discussionmentioning
confidence: 97%
“…The is similar to experience from Nepal who reported no adverse event throughout the course of the MINI programme. [30] Scale-up and implementation of PSBI treatment guideline requires government commitment and motivation of the health facility staff. If that commitment is not there in the shape of human and financial resources, this will not happen.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire tools for baseline and endline surveys were adapted from the team's own, and others' previous work on the Integrated Management of Childhood Illness [28], iCCM [29], and CBNC [30]. The questionnaire instrument included modules regarding household, health posts and health centres, HEWs, health centre staff, WDA members, an observation and re-examination of the HEW assessing sick children, and district contextual factors (Table 2) [see additional files [1][2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…This category of health workers is reportedly able to correctly manage multiple child illnesses through the integrated community case management (iCCM) activities that the government initiated in 2010 [5]. If appropriately trained and supported, this cadre can also treat severe infections of the newborn in a costeffective way within the Community-Based Newborn Care (CBNC) program that has been running since 2014 [6]. Although nearly all the HEWs throughout the country have been trained, relatively few sick newborns have been identified and treated [7].…”
Section: Introductionmentioning
confidence: 99%
“…Community health workers (CHWs) have the potential to address the barriers encountered by women and children in accessing maternal and child health (MCH) services, particularly in underserved rural areas where the shortage of professional health workers is most profound [1]. CHWs can increase coverage of maternal and child services in African settings, leading to improved maternal and child health outcomes [2,3]. In 2010, the South African government proposed to re-engineer the provision of primary health care by focusing on a small number of key priorities, including the training and deployment of a generalist CHW that would become a recognised cadre within the national health system [4].…”
Section: Introductionmentioning
confidence: 99%